Mycobacterium haemophilum as the Initial Presentation of a B-Cell Lymphoma in a Liver Transplant Patient - T. Doherty; M. Lynn; A. Cavazza; E. Sames; R. Hughes (Case Reports in Rheumatology)
A 66-year-old woman presented with pustular lesions of her face, trunk, and limbs and an acute arthritis of the knees and elbows. She had a complex medical background and had been on immunosuppressants for three years after a liver transplant. Tissue samples from her skin lesions and synovial fluid showed acid-fast bacilli. Mycobacterium haemophilum, an atypical mycobacteria, was later grown on culture. During her treatment with combination antibiotic therapy, she developed a pronounced generalised lymphadenopathy. Histology showed features of a diffuse B-cell lymphoma, a posttransplant lymphoproliferative disorder (PTLD).